(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
Today the role of mass media is increasing in modern society. The linguists broadly explore instruments of influence and strengthening expressive speech of media. The actual problems of modern linguistics are peculiarities of use and functions of expression syntax means. The article investigates the communicative pragmatic function of asyndetically structures. The features of asydeton using are studied in the information and journalistic speech. Asydeton is seen as a stylistic figure, based on the pass connecting means between the components of the sentence or text. The asyndetic connection between parts of a sentence is based on the semantic filling of parts of speech, which are incorporated in complex sentences and form semantic and intonation unity. In speech, this relationship is expressed by rhythmic and melodic means, in writing – punctuation. The emission of a conjunction of the parts before each sentence has a definite meaning and intonation shade throughout statement. The reduction syntactic structure, including asyndetically structure, promotes statements of pragmatic communicative functions: representative, declarative, affirmative, expressive, appellative and more. The interaction among asyndeton with other stylistic figures allows the speaker to single out the important piece of information, enhance the expression of certain components, provide the dynamism of speech and so on.